Tindakan Pengendara Motor Terhadap Pelanggaran Aturan Lalu Lintas Dalam Pelaksanaan E-Tilang Di Kota Batam - Sari, Sherly Ayu Puspita; Elsera, Marisa; Solina, Emmy (CV Insan Kreasi Media, 2023)
The application of e-tickets in Batam City aims to increase public awareness, especially motorcycle riders in order to reduce the number of traffic violations as in accordance with Law Number 22 of 2009 Article 272 concerning Road Traffic and Transportation. However, in reality there are still many motorbike riders who violate traffic rules when the implementation of e-tickets is implemented. This study aims to find out how motorbike riders act against traffic rules in implementing e-tickets in Batam City. The theory used in this study is the phenomenological theory by Alfred Schutz. The theory used describes the motives for actions taken by motorists who violate traffic rules. This study uses a qualitative method with a descriptive approach. Data collection techniques in this study used semi-structured interviews, observation and documentation. The sampling technique used in this study was purposive sampling of 7 informants who were considered to be able to provide informants according to the needs of researchers. The results of this study conclude that the motive for causing motorcyclists in Batam City to violate traffic is due to a lack of awareness to comply with traffic rules which results in motorists being negligent or careless so that they commit acts of violating traffic rules, lack of knowledge the motorcyclist about traffic in the form of the meaning of traffic signs and the meaning of road markings. The act of violating traffic is also caused by following other motorists who also violate traffic. The objective motive (in order to motive) of motorists violating traffic is to save time on the highway and so that they can get to their destination more quickly.